2011
DOI: 10.3945/jn.110.129403
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Flux, but Not Nitric Oxide Synthesis, Decreases in Adolescent Girls Compared with Adult Women during Pregnancy,

Abstract: NO has been proposed as a mediator of vascular expansion during pregnancy. Inability to increase NO synthesis and/or production of its precursor, arginine, may contribute to pregnancy-induced hypertension. Adolescents have a higher incidence of gestational hypertension. It is not known whether pregnant adolescents can produce sufficient arginine to meet overall demands. Our objective was to measure and compare the arginine flux and NO synthesis rates of pregnant adolescents and adult women. Arginine, citrullin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…They infused patients with a combination of [guanidino- 15 N 2 ] arginine and [5,5- 2 H 2 ] citrulline or [ 15 N] citrulline alone. This combination of labeling was used to estimate NO synthesis from arginine, arginine production from citrulline in the urea cycle, and arginine from dietary sources [89]. These techniques provide researchers with a powerful arsenal to understand NO metabolism quantitatively and performing dose-response analysis of NOS inhibitors or NO-donors to design effective therapeutic treatments.…”
Section: Figure 1 Key Figurementioning
confidence: 99%
“…They infused patients with a combination of [guanidino- 15 N 2 ] arginine and [5,5- 2 H 2 ] citrulline or [ 15 N] citrulline alone. This combination of labeling was used to estimate NO synthesis from arginine, arginine production from citrulline in the urea cycle, and arginine from dietary sources [89]. These techniques provide researchers with a powerful arsenal to understand NO metabolism quantitatively and performing dose-response analysis of NOS inhibitors or NO-donors to design effective therapeutic treatments.…”
Section: Figure 1 Key Figurementioning
confidence: 99%
“…Thus, as correctly pointed out by King (3), if dietary protein intake is below some threshold required for metabolic adaptations, then women have an increased risk of poor pregnancy outcomes and appropriate nutritional intervention with adequate protein and amino acids may be necessary. Indeed, current work from Thame and Kurpad and colleagues has shown that amino acid kinetics are altered during adolescent pregnancy and in adult pregnancy with low BMIs, such that the metabolic adaptations are not adequate to sustain a healthy pregnancy outcome (16)(17)(18)(19). Thus, identifying optimal protein and amino acid requirements during different stages of pregnancy is critical for the creation of adequate dietary intake recommendations during this crucial life stage.…”
Section: Protein Metabolism During Pregnancymentioning
confidence: 99%
“…Isotopic measurements were made on plasma samples. For Protocols 1 and 2, the dansylated derivatives of arginine, citrulline, ornithine, and phenylalanine were prepared as previously described (12,13) and analyzed by LC-MS/MS monitoring the following precursor and product ions: for DANS-arginine, ions m/z 410 -392 (from guanido-15 N 2 -arginine tracer), and 410 -72 (for arginine derived from 5,5-2 H 2 -citrulline); for DANS-citrulline, ions m/z 410 -392 (from guanido-15 N 2 -arginine tracer), and 411 -72 (from 5,5-2 H 2citrulline tracer); for DANS-ornithine ions m/z, 601 -170 (from 15 N 2ornithine tracer); for DANS-phenylalanine ions m/z 404 -170 (from 2 H 5 -phenylalanine tracer).…”
Section: Mass Spectrometric Analysismentioning
confidence: 99%